2018
DOI: 10.1111/iej.12926
|View full text |Cite
|
Sign up to set email alerts
|

Is mepivacaine as effective as lidocaine during inferior alveolar nerve blocks in patients with symptomatic irreversible pulpitis? A systematic review and meta‐analysis

Abstract: This study aimed to compare the effectiveness of mepivacaine and lidocaine for pulpal anaesthesia and pain control when administered via an inferior alveolar nerve block during the root canal treatment of mandibular molars in patients with symptomatic irreversible pulpitis. A research protocol was developed and registered in PROSPERO. The systematic search was conducted during May 2017 in eight databases. The studies were selected based on inclusion and exclusion criteria. Two examiners analysed the sample ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…There are contradictory results when separate systematic reviews and meta-analyses reported their results comparing various anaesthetic solutions. A systematic review and meta-analysis reported no significant difference between lidocaine and mepivacaine as anaesthetic solutions for IANB (Vieira et al, 2018). Another systematic review and meta-analysis with a low risk of bias reported that mepivacaine and articaine were the anaesthetic solutions that could significantly improve IANB anaesthesia compared with lidocaine, but there was no significant difference for IANB success rates when other anaesthetic solutions (i.e.…”
Section: Type Of Anaesthetic Solutionsmentioning
confidence: 99%
“…There are contradictory results when separate systematic reviews and meta-analyses reported their results comparing various anaesthetic solutions. A systematic review and meta-analysis reported no significant difference between lidocaine and mepivacaine as anaesthetic solutions for IANB (Vieira et al, 2018). Another systematic review and meta-analysis with a low risk of bias reported that mepivacaine and articaine were the anaesthetic solutions that could significantly improve IANB anaesthesia compared with lidocaine, but there was no significant difference for IANB success rates when other anaesthetic solutions (i.e.…”
Section: Type Of Anaesthetic Solutionsmentioning
confidence: 99%
“…Por último, siete revisiones sistemáticas se incluyeron para la presente revisión sistemática tipo paraguas (Bartlett et al 2016 (18) , Allahem et al 2020 (19) , Su et al 2016 (20) , Nagendrababu et al 2019 (21) , Larocca et al 2019 (22) , Vieira et al 2018 (23) , Tupyota et al 2018 (24) . De los estudios seleccionados se extrajo la siguiente información: autores, título, revista, año (Tabla 2), así como número de artículos, criterios de revisión, si realizaron meta análisis o no, método de evaluación anestésica, y resultado (Tabla 3).…”
Section: Resultsunclassified
“…En el meta análisis general de Nagendrababu et al 2019 la mepivacaína con epinefrina se comportó mejor que la lidocaína con epinefrina, teniendo una mayor tasa de éxito y también se clasificó como la mejor entre otras soluciones anestésicas, además, la articaína tuvo mejores resultados que la lidocaína. Los hallazgos de Vieira et al 2018 (23) sugieren que el éxito del IANB en pacientes con pulpitis irreversible sintomática no depende exclusivamente del tipo de agente anestésico utilizado, también pueden influir aspectos como la experiencia clínica del operador y el estado psicológico del paciente. La conclusión de Tupyota et al 2018 (24) fue que el control del dolor son más eficaces cuando se utilizan intervenciones suplementarias además al bloqueo estándar del nervio alveolar inferior y se aumenta la dosis de anestésico.…”
Section: Discussionunclassified
“…The presence or absence of inflammation may alter the efficacy of a local anesthetic [27282930]. Vasodilation will hasten the diffusion of local anesthetic drugs away from the area, thus reducing their efficacy.…”
Section: Discussionmentioning
confidence: 99%